Gambaran Pengetahuan Orang Tua Tentang Penyakit ISPA Di Poli Anak Rumah Sakit Bhayangkara Kota Kendari - Muhammad Uksim (Jurnal Keperawatan, 2023)
Acute Respiratory Infection (ARI) is a disease that globally is the cause of the highest morbidity. Every year, 1.3 million children under five die from acute respiratory infections worldwide. ARI is one-third of under-five deaths in low-income countries. This study aims to describe parents' knowledge of ARI disease at the Children's Clinic at Bhayangkara Kendari Hospital from May to June 2022. Using a quantitative descriptive approach with a sample of 37 respondents. The results of this survey were 14 people (37.8%), parents with sufficient knowledge were 13 people (35.1%) and parents with less knowledge were 10 people (27.1%). that more parents have good knowledge about ARI disease. It is hoped that parents can improve literacy about ARI by seeking information either directly from health workers or through books or other sources of information.